2021
DOI: 10.1039/d1gc01157j
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-mediated synthesis of amides from carboxylic acids and amine-boranes

Abstract: A practical method for the amidation reaction between carboxylic acids and amines was developed, for the first time, through a visible light-mediated photoredox deoxygenation at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…To our delight, a good yield of product 3a was produced while using toluene as a solvent (entry 11). Meanwhile, we checked the effect of temperature on the reaction, and it was found that rising or falling the temperature will reduce the yield of product 3a (entries [12][13][14]. Then, Then, the loading effects of the oxidant were explored.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
See 4 more Smart Citations
“…To our delight, a good yield of product 3a was produced while using toluene as a solvent (entry 11). Meanwhile, we checked the effect of temperature on the reaction, and it was found that rising or falling the temperature will reduce the yield of product 3a (entries [12][13][14]. Then, Then, the loading effects of the oxidant were explored.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…Flash column chromatography was generally performed on silica gel (200-300 mesh) and the progress of the reaction was monitored by thin-layer Template for SYNTHESIS Thieme chromatography (TLC). NMR spectra ( 1 H NMR at 400 MHz, 13 C NMR at 100 MHz) were recorded on a Bruker Inova-400 instrument using tetramethylsilane (TMS) as an internal standard, chemical shifts (in ppm) were referenced to CDCl3 (δ=7.26 ppm). High-resolution mass spectrometry (HRMS) data were performed at a Micromass Q-TOF Global Tandem Mass Spectrometer.…”
Section: Scheme 3 Mechanistic Studymentioning
confidence: 99%
See 3 more Smart Citations